Innovation Capability: From Technology Development to Transaction Capability - Paulo Antônio Zawislak; André Cherubini Alves; Jorge Tello-Gamarra; Denise Barbieux; Fernanda Maciel Reichert (Journal of Technology Management & Innovation, 2012)
The firm’s role, besides producing goods and services, is to promote technological change and innovation. While academic research on technological capabilities has led to a better understanding of the process of technical change itself, there is no consensus on the ultimate definition of innovation capability. The purpose of this paper is to present a framework for innovation capability. This is formed by four key capabilities (technology development, operations, management and transaction) that enable firms to reach Schumpeterian profits. Given that the study is characterized as a theoretical paper, methodologically is supported on an extensive literature review. Our main findings can be summed up in three aspects: (1) every firm has all four capabilities; none of them are null; (2) to be innovative, at least one of the firm’s capabilities must be predominant; (3) any firm, when established, is primarily technological or transactional, in a second stage, operational or managerial.